Lxx Judith: Removing the fourth wall - Allen, Nicholas P. L. (HTS teologiese studies, 2023)
Given the strong mimetic and dramatic qualities found in Judith the authors make the suggestion that perhaps, before LXX Judith became a fixed, written text, the basic fabula might well have been part of an oral tradition. The authors accept that an appropriately written dramatic work, whether transmitted through reading or an oral presentation, by means of its performative qualities, has the potential to achieve immediacy. Here, the audience may become captivated with its own familiarity and memory of popular, communally shared narratives. Accordingly, this article attempts to find evidence in the Greek text of LXX Judith for a possible oral precursor. In this context, corroboration is sought for the employment of verbal aspect and mood of the Greek language as well as instances of drama, theatrics, bodily gestures, mnemonic devices or special emphasis on the employment of the senses such as sight, taste and smell. The authors suggest that based on an analysis of the text of Chapter 13, there is much circumstantial evidence for the Judith fabula once being an oral narrative – one that embodies the dramatic and even encourages audience participation. This characteristic strongly suggests the removal of the fourth wall – the notion of an imaginary boundary between any fictional work and its audience.Contribution: This article shows that Judith 13 is indeed the climax of the narrative. However, it goes further. It is a vivid scene with various performative aspects. There are props, dialogue and audience participation. This research is cutting-edge and paves the way for new explorations.